Flexor tendon contractures in an insulin-dependent diabetic young girl (Rosenbloom syndrome) - Hasçelik, Zafer; Lök, Veli (The Turkish Journal of Pediatrics, 1987)
Limited mobility in the fingers of an insulin-dependent diabetic young girl is presented. Special localization of the contractures, fusiform swelling, normal laboratory findings and limited response to conservative treatment are important characteristics of Rosenbloom syndrome. In addition Dupuytren contractures and palmar fascial changes frequently seen in diabetes were not observed.
Keywords: childhood; diabetes mellitus; flexor tendon contractures; Rosenbloom syndrome